Analisis Kemampuan Representasi Visual Siswa dalam Menginterpretasi Diagram Siklus Hidup Bryophyta: Analisis Kemampuan Representasi Visual Siswa dalam Menginterpretasi Diagram Siklus Hidup Bryophyta - Susanti, Dewi; Rahmat, Adi (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Visual representation is important for scientific communication. One form of visual representation is a diagram. When representing diagrams, there are still students who fail to read labels or titles, misunderstand color codes, or follow arrows in the wrong direction. The aim of this research is to analyze students' ability to visually represent and interpret the Bryophyta life cycle diagram. The visual representations analyzed are internal and external visual representations. This study uses a descriptive approach involving one biology teacher and 33 students from grades X, XI, and XII at one of the high schools in the city of Bandung. Data were obtained through worksheets and semi-structured interviews. Internal visual representation is obtained from the activity of reading and re-representing the available diagrams, while external visual representation is obtained from the activity of redrawing the Bryophyta diagram based on one's own understanding. Assessment is conducted based on three main indicators: the number of phases, the sequence of phases, and the accuracy of phase descriptions. Scores are converted into percentages and categorized into five levels of proficiency: very good, good, moderate, poor, and very poor. The analysis results show that the internal visual representation of students in grades X, XI, and XII falls into the poor category, while the external visual representation of students in grades X and XI falls into the good category, and grade XII falls into the moderate category. The analysis also shows a relationship between visual representation and prior knowledge. These findings have important implications for the development of visual-based learning and mapping students' difficulties in understanding diagrams.